Ethics and politics: cases and comments - Gutmann, Amy; Thompson, Dennis F. (Nelson-Hall Publishers, 1997)
Verlagsinfo: Learn to recognize and assess the strengths and weaknesses of moral arguments in the making of public policy with ETHICS AND POLITICS: CASES AND COMMENTS. You'll find coverage of the ethics of process: the morally questionable means - violence, deception, and corruption - that are most commonly used by public officials, as well as the ethics of policy: the valuable but often competing ends that public officials strive to achieve. Conflicting values, scarce resources, and stakes as high as life and death combine with the duties of public office to make choices among policy goals controversial and morally difficult. Each ethical issue is paired with case studies in contemporary American politics.